supervisory control system for clients whit remote access of autonomous photovoltaic solar sistems - Figueroa-Cuello, Alberto Nicolás; Pardo-García, Aldo; Díaz-Rodríguez, Jorge Luis (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The Autonomous Photovoltaic Solar Systems (APSS), in spite of its disadvantages, offers some inconveniences, being the main one of them, the lack of an energy control system to optimize its operation. This work presents the analysis and design of a Remote Access Supervisor Control System, RASCS for customers with remote access of 500 W photovoltaic solar systems. The RASCS's function is to measure and manage the energy consumed by the users of APSS. For this reason, three main variables are considered: the time of connection and disconnection per load and per day, authorized to the user; the current consumed by each device or charger authorized by the designer; the battery charge level to keep it above the proper amount for proper operation. RASCS here is a system that ensures that it meets the design objectives, monitoring and controlling the critical variables of the customer systems. In this way, it will be possible to remotely diagnose APSS, reducing the time and costs of support and maintenance, with the completion of security, availability, versatility, economy, robustness and reliability to all users of these alternative energy sources.